(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Excessive harmful and unhealthy weight-control behaviors have potential serious consequencesdue to impact on their life style. Specifically dieting is considered a major risk factor for eating disorders.Unhealthy dieting can also decrease intake of energy and essential nutrients .Objective: The study aimed to identify the adolescents’ lifestyle, and reasons of skipping essential mealsand find out the relationship between adolescents’ lifestyle and reasons of skipping essential meals and theirdemographic data (gender and Body Mass Index).Methodology: A descriptive study design was conducted on impact of lifestyle and reasons of skippingessential meals upon adolescents’ Body Mass Index in secondary schools at Baghdad city, starting from20th of April 2013 to the end of October 2014. Non- probability (purposive) sample of 1254 adolescentswere chosen from secondary schools of both sides of Al-Karkh and Al-Russafa sectors. Data was collectedthrough a specially constructed questionnaire format include (20) items multiple choice questions. Thevalidity of the questionnaire was determined through a panel of experts related to the field of the study, andthe reliability through a pilot study. The data were analyzed through the application of descriptive statisticalanalysis frequency, & percentages, and inferential statistical analysis, chi-square, are used.Results: Regarding the gender, finding indicates that males and females (48.7, and 51.3%) respectively,were approximately equal, and the result study samples find more than one forth BMI were almost equal inunder and normal weight percentile (27.8%, and 27.8%) respectively, they spent mostly time (5 hours andmore) in watching TV, and use the computer for playing games, and sometimes eat during watching TV orplaying computer games. Adolescents’ gender has highly significant association with times sharing withphysical activity per week but the other items have no significant association. Adolescents’ Body Mass Indexhas highly significant association with their lifestyle. Adolescents’ gender has highly significant associationwith the reasons of skipping breakfast meal and the adolescents’ Body Mass Index have no significantassociation with the reasons of skipping meals